Faktor-Faktor Yang Mempengaruhi Audit Delay Pada Perusahaan Manufaktur Sektor Aneka Industri - Ikhsan Galih Alazis; Riana Rachmawati Dewi; Yuli Chomsatu (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Delays in auditing financial reports within companies can be a cause of overall delays in issuing company reports, but audits will be necessary to ensure the accuracy and transparency of financial reports published by companies. Many factors trigger the emergence of audit delay. So researchers want to learn more about the effect of variables profitability, solvency, company size, audit opinion, and auditor reputation on audit delays. The researcher chose the population in manufacturing companies in the various industrial sectors listed on the Indonesia Stock Exchange (IDX) 2019-2021. The data analysis technique in this research is multiple linear regression. Sampling method with purposive sampling with the number of samples used 93 companies that have complied with the sampling. This study proves that profitability, company size, audit opinion affect audit delay while solvency and auditor reputation do not affect audit delay. Keywords: Profitability, Solvency, Company Size, Audit Opinion, Auditor Reputation, Audit delay.